PENGARUH MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV A SDN PETUKANGAN UTARA 07 - Kinanti Fadya Nema; Lutfi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on the reading comprehension ability of grade IV A students at SDN Petukangan Utara 07. This study used a pre-experimental method with a one-group pretest-posttest design, involving 30 students. The results of the pretest and posttest were analyzed using prerequisite analysis tests and hypothesis tests. The normality test was carried out using the Shapiro-Wilk test and showed that the data were normally distributed. The hypothesis test using a paired sample t-test obtained a sig. (2-tailed) result of 0.000 <0.05, so H₀ was rejected and H₁ was accepted. This indicates that there is a significant difference between the pretest and posttest scores of students. In addition, the results of the N-Gain analysis showed that the increase in reading comprehension ability was in the moderate category. Thus, the results of this study conclude that the Cooperative Integrated Reading and Composition (CIRC) learning model has an effect on improving the reading comprehension skills of fourth-grade students at SDN Petukangan Utara 07.